Face Masks for All and All for Face Masks in the COVID-19 Pandemic: Community Level Production to Face the Global Shortage and Shorten the Epidemic - Missoni, Eduardo (Disaster Med Public Health Prep, 2020)
The current coronavirus disease 2019 (COVID-19) pandemic caused a global shortage of medical masks, leaving most exposed health personnel without appropriate protection. Since the beginning of the outbreak, the World Health Organization WHO) has revised several times the recommendations on general use of facemasks. Until recently, WHO recommended to limit the use of facemasks to symptomatic people and advised against off-standard solutions. Moreover, recommendations differ among and within countries, causing public confusion and individual initiative. There is wide consensus that universal appropriate use of masks may contribute both to contain the epidemic and to reduce the burden on national procurement, if a community production approach is followed. Especially in low-middle income countries, due to the scarce capacity of national industrial production or import, the use of masks produced at community level may become the only viable option. For the purpose ad hoc guidelines will be needed. Current knowledge and experience call for further and updated review of global and national guidelines to provide clear and consistent criteria to ensure the widest availability and appropriate use of facial protection, bearing in mind populations in socio-economic disadvantaged settings.